2008
DOI: 10.1042/bj20081336
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein induces lipogenic transcription factor SREBP1 and fatty acid synthase through the activation of nuclear receptor LXRα

Abstract: HBV (hepatitis B virus) is a primary cause of chronic liver disease, which frequently results in hepatitis, cirrhosis and ultimately HCC (hepatocellular carcinoma). Recently, we showed that HBx (HBV protein X) expression induces lipid accumulation in hepatic cells mediated by the induction of SREBP1 (sterol-regulatory-element-binding protein 1), a key regulator of lipogenic genes in the liver. However, the molecular mechanisms by which HBx increases SREBP1 expression and transactivation remain to be clearly el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 58 publications
3
99
1
1
Order By: Relevance
“…1C). A similar observation was reported in a recent article 30 that was published during the processing of this article.…”
Section: Resultssupporting
confidence: 69%
“…1C). A similar observation was reported in a recent article 30 that was published during the processing of this article.…”
Section: Resultssupporting
confidence: 69%
“…Besides papers that claimed suppression of viral replication by NAFLD, there are also studies that reported an increase in the rate of NAFLD with HBV (21,(23)(24)(25)(26). HBV X protein (HBx) has been shown to increase the transcription of sterol regulatory element-binding protein-1c (SREBP-1c) and peroxisome proliferator-activated receptor (PPAR) (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that hepatitis B virus X protein induces lipogenic genes through the activation of LXRa. 42 Thus, hepatitis B virus X protein physically interacts with LXRa in the nucleus and enhances the binding of LXRa to LXRE (LXR-response element). 43 In this study, core and NS5A are mainly detected in the cytoplasm of replicating cells, as previously described.…”
Section: Discussionmentioning
confidence: 99%